2017
DOI: 10.21161/mjm.98716
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome analysis of Klebsiella: Unique genes associated with isolates from Indonesian tempeh

Abstract: Aims: Our previous study demonstrated that Klebsiella IIEMP-3 associated with tempeh was genetically different from those of medical isolates. In addition to the whole genome sequence of Klebsiella IIEMP-3, the draft genome sequence of another isolate, i.e. IWJB-6 was employed for comparison. In this study, the details of the virulence genes and unique gene in both Klebsiella isolates were compared employing in silico and in vitro analysis. Methodology and results: Whole genome of Klebsiella IIEMP-3 and IWJB-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…pneumoniae isolates from Indonesian tempeh could be considered as non-pathogenic group (Cesrany et al, 2017). This study also suggested that K. pneumoniae in fresh tempeh were primarily originated from soybean which also serves as the main ingredient of traditional tempeh.…”
Section: The Source Of Enterobacteriaceae In Tempehmentioning
confidence: 60%
“…pneumoniae isolates from Indonesian tempeh could be considered as non-pathogenic group (Cesrany et al, 2017). This study also suggested that K. pneumoniae in fresh tempeh were primarily originated from soybean which also serves as the main ingredient of traditional tempeh.…”
Section: The Source Of Enterobacteriaceae In Tempehmentioning
confidence: 60%
“…In Indonesia, harmless Klebsiella spp. that did not have virulence‐associated genes, for example, rmpA , could be found in most tempehs (Cesrany, Yulandi, Rusmana, & Suwanto, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Among these MAGs, five were in the species level of taxonomic rank. Some K. pneumoniae isolates from EMP and WJB tempeh fully sequenced and subjected to genomic comparison to pathogenic strain in the previous study [ 30 ]. K. pneumoniae is known to produce vitamin B 12 during tempeh fermentation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%